2013
DOI: 10.1002/pbc.24819
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary outcomes in survivors of childhood central nervous system malignancies: A report from the childhood cancer survivor study

Abstract: Background Adult survivors of childhood Central Nervous System (CNS) tumors may be at risk for pulmonary dysfunction. This study enumerates the incidence of pulmonary dysfunction and explores associations between craniospinal irradiation (CSI) and pulmonary dysfunction among survivors of childhood CNS tumors. Methods Participants included Childhood Cancer Survivor Study (CCSS) cohort members treated for CNS malignancies when < age 21, who survived five+ years, and sibling comparisons. Medical records were ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 35 publications
1
36
1
Order By: Relevance
“…Few studies have included age-and sex-matched noncancer controls, 9,10 and none have examined the impact of abnormal lung function on health-related quality of life The Children's Oncology Group (COG) Long-Term FollowUp (LTFU) Guidelines 1,13 recommend that survivors exposed to pulmonary-toxic therapy undergo a one-time pulmonary function testing (PFT) and symptom assessment at the time of transition into LTFU care, with subsequent testing as clinically indicated. However, a paucity of information regarding the trajectory of change in pulmonary function with time has precluded the development of guidelines regarding the frequency and duration of subsequent screenings.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have included age-and sex-matched noncancer controls, 9,10 and none have examined the impact of abnormal lung function on health-related quality of life The Children's Oncology Group (COG) Long-Term FollowUp (LTFU) Guidelines 1,13 recommend that survivors exposed to pulmonary-toxic therapy undergo a one-time pulmonary function testing (PFT) and symptom assessment at the time of transition into LTFU care, with subsequent testing as clinically indicated. However, a paucity of information regarding the trajectory of change in pulmonary function with time has precluded the development of guidelines regarding the frequency and duration of subsequent screenings.…”
Section: Introductionmentioning
confidence: 99%
“…35 Similarly, after a median of 18 years of follow-up among childhood cancer survivors treated with bleomycin, Mulder et al found pulmonary function impairments in 44% of survivors. 36 37 Finally, using a comprehensive systematic clinical assessment, Hudson et al found that the prevalence of adverse outcomes by organ system among adult survivors of childhood cancer was highest for the pulmonary system, with abnormal pulmonary function found in 65.2% of survivors after a median time from diagnosis of 25 years. 38 …”
Section: Pulmonary Limitationsmentioning
confidence: 98%
“…This puts long term survivors at significant risk of long term sequelae of RT as they age. The sequelae include hearing loss, cardiac disease, hypothyroidism, neurocognitive decline, vertebral body impaired growth, or secondary malignancies …”
Section: Introductionmentioning
confidence: 99%